Reading the Bromance : Homosocial Relationships in Film and Television (Book collections on Project MUSE., 2014)
This book discusses how the concept of "bromance" emerged as a term denoting an emotionally intense bond between straight men. The book analyses films ranging from I Love You, Man to Superbad, Humpday, I Now Pronounce You Chuck and Larry, The Hangover, and the Jackass films, and include studies of representative examples in international cinema such as Y tu mama tambien and classic and contemporary films of the Bollywood genre. It also examines the increasingly prevalent appearance of the bromance phenomenon in television narratives, from the "male bonding" rituals of Friends and Seinfeld to more recent manifestations of The Wire and the MTV reality series Bromance.